(untitled) (Colloquia Comparativa Litterarum, 2025)
Where does the eastern frontier of European literature lie? This is the big question posed by Lesya Ukrainka (1871–1913). Although she defended Ukrainian as a literary language, she was at odds with traditionalist Ukrainophiles in that she wanted to develop a Ukrainian literature that was modern through its Europeanness. Hence her polyglottism, her intense activity as a translator, and the fact that she made her own work a truly polyglossic space.